Association Between Dietary Quality and Postpartum Depression in Lactating Women: A Cross-Sectional Survey in Urban China - Yang, Chenlu; Zhao, Ai; Lan, Hanglian; Ren, Zhongxia; Zhang, Jian; Szeto, Ignatius Man-Yau; Wang, Peiyu; Zhang, Yumei (Frontiers in Nutrition, 2021)
Background: Evidence on the effects of dietary quality on the risk of postpartum depression in the Chinese population is limited. This study aimed to examine the association between dietary quality and postpartum depression in Chinses lactating women. Methods: A total of 939 participants from 10 cities were included in this analysis. A one-time 24-h dietary recall was used to obtain the data on food consumption and dietary quality was assessed based on Diet Balance Index. The Edinburgh postnatal depression scale was considered at a cutoff point of 10 to detect postpartum depression. Poisson regression models were used to explore the association of dietary quality with postpartum depression. Results: Depressed women tended to have a more inadequate intake of vegetables and have more insufficient food variety. The median (25th, 75th) of the overall high bound score (HBS), low bound score (LBS), and diet quality distance (DQD) was 9 (5, 14), 30 (25, 37), and 40 (34, 47), respectively. Compared with subjects with the lowest quartile of LBS, those with the highest quartile of LBS had a higher risk of postpartum depression [adjusted prevalence ratio (aPR), 1.08; 95% confidence interval (95% CI), 1.01, 1.15; P for trend, 0.043]. We also observed a significant association between DQD and postpartum depression (Q4 vs. Q1: aPR, 1.07; 95% CI: 1.00, 1.14; P for trend, 0.036). Conclusion: Poor dietary quality was associated with postpartum depression in Chinese lactating women.